Impact of Clinical Pharmacist-Led Interventions on Short Term Quality of Life among Breast Cancer Women Taking Chemotherapy - Karrar Harith Alkashaf; Imad Mohammed, Samer (Iraqi Journal of Pharmaceutical Sciences, 2024)
Abstract: Background: Drug toxicity and chemotherapeutic side effects negatively impact the quality of life of breast cancer patients. Objectives: to evaluate the efficacy of pharmaceutical Interventions (PI) on quality of life (QOL)Among chemotherapy intake breast cancer women. Method: A pre-post interventional study was carried out at the chemotherapy ward of Alhabobi Hospital in Alnasiriyah City. Eligible patients received comprehensive pharmaceutical care and a self-compiled Breast Cancer Patients Medication Knowledge Guide pamphlet. Each patient received two sessions, the first at baseline and the second after 7, 14, or 21 days depending on the next taking dose of chemotherapy. Each session lasted for approximately 15-30 minutes. Participants were asked to complete a QOL Questionnaire(EORTC QLQ-C30) before and after study time. Results: Fifty women with breast cancer were enrolled in the interventional group, and all of these patients ultimately completed the study, at the end of the study, the five functional scales (physical, role, emotional, cognitive, and social), were significantly increased after the intervention by the clinical pharmacist. The three symptom scales (fatigue, nausea/vomiting, and pain) were significantly decreased after the study. In addition, six individual measurement project scores were decreased at the end of the study. However, constipation was the only intervention that had no effect. Conclusion: a clinical pharmacist-led educational intervention may enhance the quality of life of breast cancer patients and play a crucial role in reducing chemotherapy-related complications and adverse effects.